ANALISIS PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN DALAM INDEKS LQ 45 Tahun 2010-2013 - Ade Affinanda; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2015)
This study seeks to learn some financial ratios that can be used as a predictor of short return on investment. The object of research used in this study is a company incorporated in the LQ 45 during the 2010-2013 study periode. The variables studied were Profitability and Solvency. The analysis technique used in this research is multiple linear regression.This research was conducted with quantitative methods on the financial statements of listed companies in the LQ 45 during the period 2009-2010. The total sample was 19 companies, which are determined through purposive sampling method. Method of hypothesis testing using different test t-test and linear regression.Results of research in line with the results of research conducted by Yeye (2011). The results of this study showed no positive effect between the Gross Profit Margin (GPM), Net Profit Margin (NPM), return on assets (ROA), Return on Equity (ROE), and Debt To Equity (DER) toreturn stock companies listed in LQ45 on Indonesia Stock Exchange during the period 2010-2013.